1955
DOI: 10.1084/jem.102.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Neuritis: An Experimental Disease of Rabbits Induced by the Injection of Peripheral Nervous Tissue and Adjuvants

Abstract: In experimental allergic encephalomyelitis (EAE), produced by injecting rabbits with whole rabbit spinal cord together with tubercle bacilli and mineral oil, lesions comparable to those seen in the central nervous system are found in the nerve roots, spinal ganglia, and peripheral nerves. When special fractions of bovine white matter are used as antigen in rabbits, the same distribution of lesions is seen but peripheral nerve involvement is relatively less frequent. When rabbit sciatic nerve or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
0
2

Year Published

1961
1961
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 535 publications
(133 citation statements)
references
References 18 publications
2
128
0
2
Order By: Relevance
“…Other workers have also reported demyelination in these models (Waksman and Adams 1955;Wisniewski et al 1969;Piliero and Cremonese 1973;McFarlin et al 1974;Dal Canto et al 1977). Electrophysiological studies have shown focal nerve conduction abnormalities in the DRGs and at the dorsal root entry zone in rabbits with EAE (Pender and Sears 1982, 1985, at the ventral root exit zones and in the DRGs of rats with whole-spinal-cordinduced EAE (Pender 1986a;Pender and Sears 1986) and in the sacrococcygeal dorsal roots of rats with MBP-induced EAE (Pender 1986b).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Other workers have also reported demyelination in these models (Waksman and Adams 1955;Wisniewski et al 1969;Piliero and Cremonese 1973;McFarlin et al 1974;Dal Canto et al 1977). Electrophysiological studies have shown focal nerve conduction abnormalities in the DRGs and at the dorsal root entry zone in rabbits with EAE (Pender and Sears 1982, 1985, at the ventral root exit zones and in the DRGs of rats with whole-spinal-cordinduced EAE (Pender 1986a;Pender and Sears 1986) and in the sacrococcygeal dorsal roots of rats with MBP-induced EAE (Pender 1986b).…”
Section: Discussionmentioning
confidence: 71%
“…They concluded that these reports were invalid because of the nonspecificity of clinical signs, the occurrence of intercurrent diseases, the inadequacy or incorrect timing of histologic evaluations, and the lack of controls for specificity of the signs. The present paper emphasizes that, if clinicopathological correlations are to be made in EAE, one must thoroughly examine the PNS, which is known to be affected in EAE in all species studied (Freund et al 1947;Ferraro and Roizin 1954;Waksman andAdams 1955, 1956;Levine and Wenk 1963;Wisniewski et al 1969;Piliero and Cremonese 1973;McFarlin et al 1974;Dal Canto et al 1977), as well as the CNS, particularly the lumbar, sacral and coccygeal segments of the spinal cord. The involvement of the PNS when animals are inoculated with whole CNS tissue or purified CNS MBP is explained by the fact that the P1 MBP from the PNS is similar, if not identical to, CNS MBP (Brostoff and Eylar 1972;Greenfield et al 1973).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The distribution of lesions in the PNS differs among different models of acute EAN. In rabbits and mice with acute EAN induced by inoculation with whole PNS tissue, the dorsal root ganglion is the most consistently affected region of the PNS [1,3]. The dorsal root ganglion is also a major site of involvement in rats with PNS myelin-induced or P2-induced acute EAN [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental allergic neuritis (EAN) is an autoimmune demyelinating disease of the peripheral nervous system (PNS) induced by inoculation with PNS tissue [1] or P2 protein [2] and adjuvants. In its acute form, it is widely studied as an animal model of the human disorder, the Guillain-Barré syndrome.…”
mentioning
confidence: 99%